The Influence of Online Promotion and Product Diversity on Customer Satisfaction with Purchase Decision as an Intervening Variable - Febrianto, Denni; Fihartini, Yuniarti; Husna, Nurul (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the bustling fitness industry of Bandar Lampung, Club Verde Fitness Center stands out, utilizing online promotions via Instagram to engage potential and existing customers. This quantitative study aims to assess the impact of these online promotions and product diversity on consumer satisfaction through purchase decisions. With a sample size of 141 respondents who have utilized Club Verde's facilities, data was collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that while online promotions alone didn't significantly affect consumer satisfaction, they did influence purchasing decisions. Additionally, product diversity positively impacted both purchase decisions and consumer satisfaction. These results underscore the importance of a multifaceted marketing approach and varied product offerings in enhancing consumer satisfaction and driving purchase decisions in the fitness industry.